Social Media Marketing Activities and Their Effect on Brand Loyalty Among Generations - Diana Fajarwati; Tiya Nur Haliza (Journal of Enterprise and Development (JED), 2024)
Purpose: The purpose of this study is to examine how age differences between Generation Z and Millennials influence the effectiveness of Social Media Marketing Activities (SMMA) on Consumer Brand Engagement (CBE) and brand loyalty.Method: This quantitative study utilized an online survey targeting 110 active TikTok users from Generation Z (ages 17-26) and Millennials (ages 27-42) who engage with personal care brands. Data were collected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The survey measured the impact of Social Media Marketing Activities (SMMA) dimensions—Interactivity, Informativeness, and Trendiness—on Consumer Brand Engagement (CBE) and brand loyalty.Result: The results reveal that age differences significantly influence the impact of Social Media Marketing Activities (SMMA) on Consumer Brand Engagement (CBE) and brand loyalty. While both Generation Z and Millennials respond positively to the SMMA dimensions of Informativeness and Trendiness, only Generation Z shows a significant relationship between Interactivity and CBE, highlighting distinct generational preferences in social media marketing effectiveness.Practical Implications for Economic Growth and Development: The study's findings suggest that adapting social media marketing strategies to the unique preferences of Generation Z and Millennials can enhance consumer engagement, increase brand profitability, and stimulate economic growth by promoting digital market competitiveness and encouraging innovation in the business sector.